Estimating travellers' preferences for competition in commercial passenger rail transport - Johannes Paha; Dirk Rompf; Christiane Warnecke (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
The current level of competition in European commercial passenger rail markets is low and empirical data on customer preferences in intramodal competition has hardly been available, yet. Our study raises the knowledge of competition in commercial passenger rail by exploring the determinants of customers' choice behaviour on two cross-border routes, Cologne-Brussels and Cologne-Amsterdam. We analyse stated preference information from about 700 on-train interviews by means of multinomial Logit regressions. Our analysis indicates that customers experiencing competition (Cologne-Brussels) show a higher preference for competitive services than customers for whom competition is a purely hypothetical situation (Cologne-Amsterdam). Moreover, travellers show a status quo bias, i.e. a preference for the service provider on whose trains they were interviewed which partly stems from switching costs. These findings regarding status quo bias and switching costs complement previous studies on the outcome of intramodal competition, implying that entry is even more difficult than they predicted.
Keywords: C25; D12; D40; L92; 330; competition; passenger; rail; transport; discrete choice; multinomial logit; Eisenbahnpersonenverkehr; Wettbewerb; Urlaubsverhalten; Präferenztheorie; Diskrete Entscheidung; Wechselkosten; Schätzung; Deutschland; Belgien; Niederlande